Analysis of the influence of the contact mode of the rolling elements of the slewing bearing on its stability. Issue 1 (January 2021) - Deng, Biao; Chen, Jianwei; Guo, Yang; Tang, Shengjin
Abstract: The stability of the rolling elements in the slewing bearing is an important factor that determines the smooth rotation of the slewing bearing. The slewing radius of the slewing bearing is large and the load is complicated. In this paper, the contact relationship between the rolling elements and the raceway is established by establishing a slice model of the slewing bearing. Considering the effects of axial load and radial load, respectively, the contact deformation and displacement changes of the rolling elements are analyzed. The simulation results show that the rolling elements of the two-point contact slewing bearing rotate during the load process, and the four-point contact slewing bearing is in the axial direction. Under load, the rolling contact state in the raceway with the raceway is stable without spinning; under radial load, the contact relationship between the rolling element and the four-point contact raceway at this time is essentially two-point contact, but compared to the one used Two-point contact raceway, the rolling elements have better radial stability in the newly designed raceway